2021
DOI: 10.3390/pharmaceutics13071035
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Food Effect on Oral Absorption of Efflux Transporter Substrate Drugs: Does Delayed Gastric Emptying Influence Drug Transport Kinetics?

Abstract: The oral route of drug administration is the most convenient method of drug delivery, but it is associated with variable bioavailability. Food is one of the major factors that affect oral drug absorption by influencing drug properties (e.g., solubility and dissolution rate) and physiological factors (e.g., metabolism and transport across the gastrointestinal tract). The aim of this work was to investigate the effect of food on the high-affinity intestinal efflux transporter substrate drugs. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…The liquid‐filled formulation of the lipophilic ACT‐1014‐6470 could have served as a reservoir, continuously providing a new drug that was swiftly absorbed. Fed conditions allowed for a larger amount of drug to be kept solubilized before absorption supported by food constituents and secreted bile micelles 36–38 . For other lipophilic compounds that are subjected to a large exposure increase after administration under fed conditions, such as anti‐helminthics or malaria treatments, PK models captured the effect of food by improvements of bioavailability of more than 100% under fed conditions 39 and addition of a transit compartment for a t max delay 40,41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid‐filled formulation of the lipophilic ACT‐1014‐6470 could have served as a reservoir, continuously providing a new drug that was swiftly absorbed. Fed conditions allowed for a larger amount of drug to be kept solubilized before absorption supported by food constituents and secreted bile micelles 36–38 . For other lipophilic compounds that are subjected to a large exposure increase after administration under fed conditions, such as anti‐helminthics or malaria treatments, PK models captured the effect of food by improvements of bioavailability of more than 100% under fed conditions 39 and addition of a transit compartment for a t max delay 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Fed conditions allowed for a larger amount of drug to be kept solubilized before absorption supported by food constituents and secreted bile micelles. [36][37][38] For other lipophilic compounds that are subjected to a large exposure increase after administration under fed conditions, such as anti-helminthics or malaria treatments, PK models captured the effect of food by improvements of bioavailability of more than 100% under fed conditions 39 and addition of a transit compartment for a t max delay. 40,41 For ACT-1014-6470, the estimated lag time was longer under fed conditions compared to fasted conditions in the final PK model.…”
Section: Simulationmentioning
confidence: 99%
“…Oral drug delivery systems are an economically viable way to treat the rising number of chronic conditions ranging from heart diseases to type II diabetes. However, drug absorption from the gastrointestinal (GI) tract is complex and variable (von Erlach et al, 2020); and can be influenced by internal patientspecific factors such as age, sex, disease state and importantly, external factors such as diet and food intake (Madla et al, 2021;Sharma and Prasad, 2021;Stillhart et al, 2020). The intake of food with orally administered drugs can alter the rate and/or extent of oral bioavailability, relative to the fasted state, referred to as the food effect (Koziolek et al, 2019;O'Shea et al, 2019;Varum et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Biopharmaceutical Classification System (BCS) and Biopharmaceutical Drug Disposition Classification System provide a useful predictor of potential food effects as a result of that. This led to the assumption that especially for drugs with high bioavailability, an overall delay in T max and reduced C max can be associated with delayed gastric emptying. , Sharma and Prasad added to this and demonstrated that delayed gastric emptying can influence drug transporter kinetics …”
Section: Introductionmentioning
confidence: 99%
“…1,4 Sharma and Prasad added to this and demonstrated that delayed gastric emptying can influence drug transporter kinetics. 5 Oral medicines usually have to be administered repeatedly, usually chronically, and often spread over two or even more daily doses, so it is not uncommon for the medicines to be administered in different prandial states. In addition, meals can vary significantly in terms of calorie content, volume, and nutrient composition, resulting in food effects that vary in intensity and sometimes even point in different directions.…”
Section: Introductionmentioning
confidence: 99%